Numerical analysis of SiO2 nanofluid performance in serpentine PEMFC cooling plate - Irnie Azlin, Zakaria; Wan Ahmad Najmi, Wan Mohamed; Wan Azmi, Wan Hamzah (Science Publishing Corporation, 2018)
Proton exchange membrane fuel cell (PEMFC) is among the potential substitute to current conventional internal combustion engine (ICE) in the automotive sector due to its efficient conversion efficiency and environmental friendly. However, thermal management issues in PEMFC needs to be addressed as excessive heat in PEMFC can deteriorate its performance as well as causing dehydration to the membrane. In this study, an advanced coolant of SiO2 nanofluids was numerically studied and effect in term of the heat transfer and fluid flow behavior in a single PEMFC cooling plate is investigated. The study simulated SiO2 nanofluids in a serpentine PEMFC cooling plate. The simulation is conducted at a low volume concentrations of 0.1, 0.3 and 0.5 % of SiO2 in water and water: Ethylene Glycol (W:EG) of 60:40 as base fluids. In this serpentine cooling plate design of PEMFC, a constant heat flux is applied to mimic the actual application of PEMFC. Upon completion of the study, heat transfer and fluid flow shows that the heat transfer coefficient of 0.5 vol. % of SiO2 nanofluids has improved by 3.5 % at Reynold (Re) number of 400 as compared to the base fluid of water with an acceptable pumping power increment.